2016
DOI: 10.1007/s12671-016-0508-x
|View full text |Cite
|
Sign up to set email alerts
|

Both Trait and State Mindfulness Predict Lower Aggressiveness via Anger Rumination: a Multilevel Mediation Analysis

Abstract: Trait mindfulness, or the capacity for nonjudgmental, present-centered attention, predicts lower aggression in cross-sectional samples, an effect mediated by reduced anger rumination. Experimental work also implicates state mindfulness (i.e., fluctuations around one's typical mindfulness) in aggression. Despite evidence that both trait and state mindfulness predict lower aggression, their relative impact and their mechanisms remain unclear. Higher trait mindfulness and state increases in mindfulness facets may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 49 publications
5
50
2
Order By: Relevance
“…Impairments in some of these domains have been linked with greater levels of physical aggression, anger, and hostility in an offender sample, with stronger effect sizes for impairments in the abilities to describe internal states, act with awareness, and assume a nonjudgmental stance (Velotti et al, ). Similar negative associations between dispositional mindfulness and aggression have been documented in other populations (e.g., men seeking substance use treatment; Shorey, Anderson, & Stuart, ), as well as in longitudinal designs (Eisenlohr‐Moul, Peters, Pond, & DeWall, ). In undergraduate samples, Heppner et al () reported evidence of robust negative relationships between mindfulness and aggression, both at the trait‐level, and during a social‐rejection paradigm.…”
Section: Introductionsupporting
confidence: 68%
“…Impairments in some of these domains have been linked with greater levels of physical aggression, anger, and hostility in an offender sample, with stronger effect sizes for impairments in the abilities to describe internal states, act with awareness, and assume a nonjudgmental stance (Velotti et al, ). Similar negative associations between dispositional mindfulness and aggression have been documented in other populations (e.g., men seeking substance use treatment; Shorey, Anderson, & Stuart, ), as well as in longitudinal designs (Eisenlohr‐Moul, Peters, Pond, & DeWall, ). In undergraduate samples, Heppner et al () reported evidence of robust negative relationships between mindfulness and aggression, both at the trait‐level, and during a social‐rejection paradigm.…”
Section: Introductionsupporting
confidence: 68%
“…Dialectical behavior therapy (DBT; Linehan, 1993), an empirically supported intervention for BPD, includes training in mindfulness skills that facilitate more adaptive, present-centered responding to emotion. Increasing nonjudgment of internal experiences, a component of mindfulness emphasized by DBT, may be particularly relevant for targeting anger rumination and its outcomes (Peters, Eisenlohr-Moul, Upton, & Baer, 2013; Peters, et al, 2015; Eisenlohr-Moul, Peters, Pond, & DeWall, 2016). Given the connection between rumination and the severity of BPD features, training in these types of skills may benefit individuals struggling with BPD symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Such measures were adapted from multi-item scales that have displayed acceptable validity and reliability (Diener et al, 2010). Emotions were measured by nine items assessing anxiety, depressed, angry, bored, sad, contented, interested, happy, and relaxed, respectively (e.g., "Do you feel depressed at the moment?").…”
Section: Methodsmentioning
confidence: 99%
“…Emotions were measured by nine items assessing anxiety, depressed, angry, bored, sad, contented, interested, happy, and relaxed, respectively (e.g., "Do you feel depressed at the moment?"). Such measures were adapted from multi-item scales that have displayed acceptable validity and reliability (Diener et al, 2010). Items were rated on a Likert-type scale of 0 (not at all) to 6 (very much so).…”
Section: Methodsmentioning
confidence: 99%